Single bacterial resolvases first exploit, then constrain intrinsic dynamics of the Holliday junction to direct recombination. Issue 5 (22nd February 2021) - Ray, Sujay; Pal, Nibedita; Walter, Nils G
Abstract: Homologous recombination forms and resolves an entangled DNA Holliday Junction (HJ) crucial for achieving genetic reshuffling and genome repair. To maintain genomic integrity, specialized resolvase enzymes cleave the entangled DNA into two discrete DNA molecules. However, it is unclear how two similar stacking isomers are distinguished, and how a cognate sequence is found and recognized to achieve accurate recombination. We here use single-molecule fluorescence observation and cluster analysis to examine how prototypic bacterial resolvase RuvC singles out two of the four HJ strands and achieves sequence-specific cleavage. We find that RuvC first exploits, then constrains the dynamics of intrinsic HJ isomer exchange at a sampled branch position to direct cleavage toward the catalytically competent HJ conformation and sequence, thus controlling recombination output at minimal energetic cost. Our model of rapid DNA scanning followed by 'snap-locking' of a cognate sequence is strikingly consistent with the conformational proofreading of other DNA-modifying enzymes.